Intrinsic Cerebro-Cerebellar Functional Connectivity Reveals the Function of Cerebellum VI in Reading-Related Skills - Ang, Chen; Zhang, Jia; Chu, Mingyuan; Li, Hehui; Tian, Mengyu; Feng, Xiaoxia; Zhang, Manli; Liu, Li; Meng, Xiangzhi; Ding, Guosheng (Frontiers in Psychology, 2020)
The engagement of cerebellum VI in reading was reported in both typically developing and dyslexic readers. However, it is still not clear how the cerebellum VI contributes to reading. Here we examined the correlation of intrinsic cerebro-cerebellar functional connectivity with two critical reading-related skills: phonological awareness (PA) and rapid automatized naming (RAN), with fMRI technology. Specifically, we tested the hypothesis that cerebellum may contribute to reading either by phonological skill or by automatising skill. We chose the left and right cerebellum VI as ROIs, and calculated the intrinsic cerebro-cerebellar functional connectivity during a resting state. We further explored whether and how cerebro-cerebellar resting state functional connectivity (RSFC) is associated with individuals’ reading-related skills including PA and RAN. The results showed that the functional connectivity between the left supramarginal gyrus and bilateral cerebellum VI was related to RAN, and the connectivity between left insula and right cerebellum VI was related to PA. However, the effect of PA did not survive after the RAN was regressed out. Control analyses further confirmed that it was the intrinsic cerebro-cerebellar functional connectivity rather than the local cerebellar functionality that associated with phonological awareness ability and rapid automatized naming ability. For the first time, the relationship between cerebro-cerebellar resting state functional connectivity and specific reading-related skills is explored, which deepens our understanding of the way the cerebellum VI is involved in reading.